Educação corporativa: um estudo sobre modelos de avaliação de programas - Marinelli, Marcos (2006)
This study reports on the generation and systematization of knowledge, leading to conceptual reflections, both theoretical and applied, regarding the evaluation of educational programs and of corporative education. The issue involves two questions: 1) Which models of evaluation of educational programs and of corporative education have been brought to light and described in Portuguese and English literature since the model presented by Kirkpatrick (1959)? and 2) Have these models shown theoretical consistency as for the elements and phases that they comprise, or there are new ways to evaluate programs in corporative education? The overall objective of this dissertation involves the presentation, analysis and comparison of the models of the evaluation of both educational programs and programs in corporative education present in Portuguese and English literature, produced since 1959, and which have been presented as instruments aimed at the evaluation of educational programs and programs in corporative education. This dissertation was carried out on the basis of a “quadripolar” methodology which was composed of the following poles: epistemological, theoretical, morphological and technical. The epistemological pole is based on Bachelardian philosophy which assumes that science and its object are not given, but are on the process of being constructed; thus the object to be analyzed is flexible to be reexamined and open to propositions toward its betterment. The theoretical pole indicates that the evaluation of programs in corporative education is part of a field of recent study, with more significant contributions to learning effects on the performance of trainees, paying less attention to the investigation of the effects on the group, the work units and the organizations alike. Further, it presents more recent contributions in English literature to the models of evaluation of programs in corporative education from Kirkpatrick and Hamblin. At the morphological pole, six evaluation models of educational programs, fifteen models of evaluation of corporative education programs and one model of evaluation of multilevel programs are described. The technical pole presents the methodology used (bibliographic review, with content analysis), the analysis of evaluation models of programs in education and in corporative education, as well as five secondary studies. The final considerations confirm the assumptions studied in this work, by underlining that: (1) secondary research works have substantiated that success in a program at a given level does not necessarily bring about the same successful result at the subsequent levels, calling into question the theoretical assumption that causality relations or positive correlations, and statistically significant, among the different levels of evaluation of the educational programs in Kirkpatrick and Hamblin’s models; 2) it has been found out the nonexistence of studies attempting to explain the connections among the different types of analysis (individual, group and organizational). To reach such an understanding, it would be necessary to adopt a multilevel approach to confirm, in this manner, the assumption that there are other models that explain the relations of causality and correlations among the different levels of evaluation of programs in corporate education; and, further, that (3) even though the models of evaluation of educational programs may be different, they bring within their cores the referential models of Kirkpatrick and Hamblin’s, confirming thus the assumption that both models continue serving as the basis for the formulation of the others.